A bifunctional thienyl COF composite fiber with both photocatalytic antibacterial and mustard gas simulant degradation properties and a preparation method thereof

Through the composite COF and fiber composite of the Pepholi base COF and fiber, the pylophene base COF composite fiber solves the problem of the existing technology that is difficult to effectively degrade chemical agents and resist harmful bacterial/virus infections. The potential for the application of biochemical protection products.

CN116556064BActive Publication Date: 2025-01-28FUZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310059938.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-18
Publication Date
2025-01-28
Estimated Expiration
2043-01-18

AI Technical Summary

Technical Problem

It is difficult to develop an efficient, pollution-free and easily available composite material in the prior art that can effectively degrade chemical poisons, while resisting harmful bacterial/viral infections, and responding to biohazards and chemical threats.

Method used

By compounding the pylopenic COF with the fiber, the pylophene base COF composite fiber is formed, and its wide spectrum absorption and high stability are used to achieve the photocatalytic degradation and antibacterial effects of the mustard gas simulator and harmful bacteria.

Benefits of technology

Anti-bacterial rates of more than 99%of Gram-positive and negative bacteria in Gram-positive and negative bacteria were achieved within 45 minutes of simulation sunlight, and more than 90%of the 2-CEES photocatalytic oxidation was oxidized to non-toxic subcarcan compounds within 3 hours. After 1 hour, the degradation rate is still greater than 99%after the 5 cycle washing cycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116556064B_ABST
    Figure CN116556064B_ABST
Patent Text Reader

Abstract

The present invention discloses a bifunctional thienyl COF composite fiber having both photocatalytic antibacterial and degradation of mustard gas simulants and a preparation method thereof. The present invention uses benzo[1,2-B:3,4-B':5,6-B']terthiophene-2,5,8-trialdehyde and an amino compound to synthesize a stable two-dimensional COF by a solvothermal method, and the COF is loaded on an acrylic acid-modified non-woven fabric to prepare a COF composite fiber. The COF composite fiber has an antibacterial rate of more than 99% against Gram-positive Bacillus subtilis and Gram-negative Escherichia coli under simulated sunlight, has good photocatalytic activity for the degradation of 2-CEES, and has a degradation rate of 2-CEES greater than 99% after at least 5 cycles of photocatalytic decontamination cycles. The COF composite fiber of the present invention is a potentially efficient composite material for decontaminating pathogens and chemical agents, and has great application potential in biochemical protective equipment for preventing public safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of composite fiber material products, in particular to a bifunctional thienyl COF composite fiber having both photocatalytic antibacterial properties and the ability to degrade a mustard gas simulant, and a preparation method thereof. Background Art

[0002] With the advancement of science and technology, a variety of chemical agents have been developed worldwide. The use of chemical agents can poison or kill humans, animals and plants on a large scale. Among them, mustard gas, a representative one, has caused millions of casualties since World War I. At the same time, bacterial / viral infections in public places also pose a major threat to humans. According to statistics from the World Health Organization, more than 10 million people die from infections every year. Therefore, it is particularly important to develop an efficient, pollution-free, and easily available composite material that can effectively degrade chemical agents while resisting harmful bacterial / viral infections to deal with biological hazards and chemical threats.

[0003] COF is a class of organic porous polymers with periodicity and crystallinity. COF materials are widely used in various fields due to their advantages such as high specific surface area, structural adjustability, and high stability. Compared with other materials, the composite materials formed by combining COF with fibers have the advantages of high efficiency, non-corrosiveness to skin and equipment, and high product selectivity in photocatalytic degradation of chemical agents such as mustard gas simulants and biological agent simulants such as Bacillus subtilis. Summary of the invention

[0004] The invention provides a bifunctional thienyl COF composite fiber having both photocatalytic antibacterial and mustard gas simulant (2-CEES) degradation and a preparation method thereof. The thienyl COF of the invention has a wide light absorption range, high stability, and is easy to load on a fiber material. The COF composite fiber of the invention has an antibacterial rate of more than 99% within 45 minutes against Gram-positive Bacillus subtilis and Gram-negative Escherichia coli under simulated sunlight, and has a photocatalytic activity of rapidly degrading 2-chloroethyl ethyl sulfide (2-CEES) into a non-toxic sulfoxide compound. More than 90% of 2-CEES is photocatalytically oxidized into a non-toxic sulfoxide compound CEESO within 3 hours, and a half-life of t 1 / 2 ≤1h; after 5 cycles of photocatalytic cyclic decontamination, the degradation rate of 2-CEES by the COF composite fiber of the present invention is still greater than 99%. The COF composite fiber material of the present invention has good application prospects in photocatalytic elimination of biochemical poisons and the like.

[0005] To achieve the above object, the present invention adopts the following technical solution:

[0006] A method for preparing a thienyl COF composite fiber comprises the following steps:

[0007] 1) The non-woven fabric was ultrasonically washed with acetone and NaOH solution to remove surface impurities, then rinsed with deionized water for 3 times and dried for use, then 20 mL of benzophenone ethanol solution was added to 100 mL of acrylic acid aqueous solution, stirred at room temperature, and then added to the non-woven fabric and immersed for 1 hour;

[0008] 2) taking out the non-woven fabric impregnated in step 1) and irradiating the front and back sides with a UV lamp for 0.5 h, then ultrasonically cleaning with anhydrous ethanol, and then rinsing with deionized water for 3 times and drying for later use;

[0009] 3) 9.9 mg of benzo[1,2-B:3,4-B':5,6-B']terthiophene-2,5,8-trialdehyde and 9.3 mg of an amino compound were placed in a glass tube, a mixture of benzyl alcohol and mesitylene was added, and ultrasonic treatment was performed until the monomers were evenly dispersed, followed by the addition of a catalyst acetic acid solution, ultrasonic treatment for 5 minutes, freezing the dispersion in a liquid nitrogen bath, vacuumizing and thawing in a water bath, repeating the "freeze-vacuumizing-thawing" process three times, and then sealing the glass tube by flame under vacuum, and placing the sealed glass tube in a 120°C oven for reaction for 3 days;

[0010] 4) After centrifugation of the solid obtained in step 3), the solid was extracted with tetrahydrofuran and acetone for 12 h, respectively, and dried in a vacuum oven at 80° C. for 12 h to obtain a COF red powder;

[0011] 5) placing the COF powder obtained in step 4) in an ethanol solution of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC), ultrasonically dispersing it at room temperature until it is uniformly dispersed, immersing the acrylic acid-modified non-woven fiber obtained in step 2) therein, soaking it at room temperature for 24 hours, taking it out, washing it with anhydrous ethanol three times, and drying it in a vacuum drying oven at 80° C. to obtain the thienyl COF composite fiber.

[0012] Furthermore, the non-woven fabric fiber in step 1) is made of polypropylene, polyacrylonitrile, polyamide, or PET fiber material.

[0013] Furthermore, the non-woven fabric in step 1) is cut into a circle with a diameter of 2 cm, the concentration of the NaOH solution is 0.1 mol / L, the concentration of the acrylic acid aqueous solution is 40% (volume percentage), and the concentration of the benzophenone ethanol solution is 15 mg / mL.

[0014] Furthermore, in step 2), the wavelength of the ultraviolet lamp is 365 nm.

[0015] Further, in step 3), the amount of the mixed solution of benzyl alcohol and mesitylene is 1 mL, benzyl alcohol: mesitylene (volume ratio) = 0.9:0.1, the amount of the acetic acid aqueous solution is 0.1 mL, and the concentration is 6 mol / L.

[0016] Furthermore, the amino compound in step 3) is one of 2,6-diaminoanthracene, [2,2'-bipyridine]-5,5'-diamine and 2,6-diaminoanthraquinone.

[0017] Furthermore, in step 5), the final concentration of COF powder added was 1 mg / mL, and the concentration of EDC ethanol solution was 2 mg / mL.

[0018] Application: The thiophene-based COF composite fiber material as described above is used in biochemical protective equipment for photocatalytic antibacterial and degradation of mustard gas simulants.

[0019] The structure of the thiophene-based COF material prepared by the present invention is as follows:

[0020]

[0021] The beneficial effects of the present invention are:

[0022] The present invention uses benzo[1,2-B:3,4-B':5,6-B']trithiophene-2,5,8-trialdehyde and 2,6-diaminoanthracene to synthesize a stable two-dimensional DA-BTT-COF by a solvent thermal method, and uses the unreacted terminal amino group in COF to carry out an amidation reaction with the carboxyl group on the acrylic acid-modified non-woven fabric fiber to prepare a COF composite fiber with wide spectrum absorption. Experiments have proved that the COF composite fiber of the present invention has an antibacterial rate of more than 99% within 45 minutes against Gram-positive Bacillus subtilis and Gram-negative Escherichia coli under simulated sunlight, has good photocatalytic activity for the degradation of sulfur mustard simulants, and photocatalytically degrades 2-chloroethyl ethyl sulfide (2-CEES) into CEESO within 3 hours, with a degradation rate of more than 90% and a half-life of t 1 / 2 ≤1h; after 5 cycles of photocatalytic cyclic decontamination, the degradation rate of 2-CEES by COF composite fiber is still greater than 99%, showing excellent stability. The COF composite fiber material shows great application potential in biochemical protective equipment for public safety prevention. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 XRD and UV spectra of COF powder;

[0024] Figure 2 This is the experimental diagram of the antibacterial effect of COF composite fiber on Bacillus subtilis;

[0025] Figure 3 This is the experimental diagram of the antibacterial effect of COF composite fiber on Escherichia coli;

[0026] Figure 4 The activity diagram of COF composite fiber in degrading mustard gas simulant;

[0027] Figure 5 This is the activity diagram of COF composite fiber degrading mustard gas simulant after 5 cycles. DETAILED DESCRIPTION

[0028] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0029] Example 1

[0030] 1) The polypropylene non-woven fabric was washed with acetone and 0.1 mol / L NaOH solution to remove surface impurities, rinsed with deionized water for 3 times and dried for standby use, 100 mL of 40% by volume acrylic acid aqueous solution was measured, 20 mL of 15 mg / ml benzophenone ethanol solution was added, stirred evenly at room temperature, and added to the polypropylene non-woven fabric for immersion for 1 hour;

[0031] 2) taking out the non-woven fabric impregnated in step 1) and irradiating the front and back sides with a UV lamp with a wavelength of 365 nm for 0.5 h; ultrasonically cleaning with anhydrous ethanol, then rinsing with deionized water for 3 times and drying for later use;

[0032] 3) Add 9.9 mg of benzo[1,2-B:3,4-B':5,6-B']trithiophene-2,5,8-trialdehyde and 9.3 mg of 2,6-diaminoanthracene to a 5 mL glass tube, add 0.9 mL of benzyl alcohol and 0.1 mL of mesitylene, ultrasonically treat the mixture until the monomers are evenly dispersed, add 0.1 mL of 6 mol / L acetic acid aqueous solution, ultrasonically treat for 5 minutes, freeze the solution in a liquid nitrogen bath, thaw in a water bath after vacuuming, repeat "freeze-vacuum-thaw" three times, seal the glass tube by flame, and place the sealed glass tube in an oven at 120°C for reaction for 3 days;

[0033] 4) After centrifugation of the solid obtained in step 3), the solid was extracted with tetrahydrofuran and acetone for 12 h respectively, and then dried in a vacuum drying oven at 80° C. for 12 h to obtain a COF reddish brown powder;

[0034] 5) The COF powder was dispersed in an EDC ethanol solution with a concentration of 2 mg / mL, and the final concentration of the COF powder was 1 mg / mL. The solution was ultrasonically dispersed at room temperature until uniformly dispersed. The acrylic acid-modified polypropylene non-woven fabric fiber obtained in step 2) was immersed therein for 24 hours at room temperature, washed with anhydrous ethanol three times, and dried in a vacuum drying oven at 80°C to obtain the thienyl COF composite fiber material.

[0035] like Figure 1As shown, the XRD graph shows a strong diffraction peak at 2.8°, as well as diffraction peaks at 5.0° and 7.4°, indicating that the COF has good crystallinity and proving the successful synthesis of COF; the UV spectrum shows that the COF powder has strong light absorption in the range of 200-800nm.

[0036] Example 2 Antibacterial test of COF composite fiber

[0037] A certain amount of Bacillus subtilis and Escherichia coli after recovery and passage (fourth generation strains) were placed in nutrient agar culture medium, cultured in a 37°C incubator for 18 hours, and the OD value of the corresponding strains was measured with an enzyme marker. 1 mL of the bacterial solution was placed in a test tube containing 9 mL of the culture medium, and the bacterial solution of appropriate concentration was obtained by diluting it by 10-fold dilution method. The COF composite fiber was placed at the bottom of a 12-well plate, and 1.5 mL of the bacterial solution was taken from the 12-well plate for illumination. At 0 min, 15 min, 30 min, and 45 min of illumination, 100 μL of the bacterial solution was taken from the 12-well plate and coated on the solid culture medium. The test under dark and blank conditions was used as the control group. They were placed in a 37°C incubator for 12 hours and photographed and recorded.

[0038] like Figure 2 , 3 As shown, it can be seen that compared with the control group under dark and blank conditions, the COF composite fiber of the present invention has obvious antibacterial effect on Gram-positive Bacillus subtilis and Gram-negative Escherichia coli under the irradiation of simulated sunlight, and the antibacterial rate reaches more than 99% within 45 minutes.

[0039] Example 3 Degradation of COF composite fibers 2-CEES test

[0040] After adding 40mL of deionized water, 10mL of methanol and 20μL of 2-CEES to the reactor, stir evenly, then immerse the composite fiber loaded with 10mg of COF in the reactor, and then place the reactor on a magnetic stirrer to stir it to reach adsorption equilibrium, then introduce oxygen for 10 minutes, and use a pipette to sample 2mL as the initial test liquid. Turn on the xenon lamp (wavelength range of 320-780nm), sample 2mL every 1h as the test liquid, add 2mL of chromatographic grade dichloromethane to the test liquid for extraction, take the lower layer of liquid and use high performance liquid chromatography to detect the remaining content of 2-CEES.

[0041] like Figure 4 As shown, the COF composite fibers degraded 2-CEES, converting 90% of 2-CEES into CEESO within 3 h with a half-life of t 1 / 2 ≤1h.

[0042] Example 4 COF composite fiber degradation 2-CEES cycle cleaning performance test

[0043] After the COF composite fiber photocatalytic degradation of 2-CEES experiment was carried out once, the COF composite fiber was washed with deionized water and ethanol to remove undegraded 2-CEES and degradation product CEESO, and then placed in an oven for drying. Then, the experiment was repeated 4 times according to the method of Implementation Case 3.

[0044] like Figure 5 The degradation rate of 2-CEES by the COF composite fiber is still greater than 99% after 5 cycles of photocatalytic cyclic decontamination.

[0045] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing a thienyl COF composite fiber, characterized in that: The steps include: 1) The non-woven fabric was ultrasonically washed with acetone and NaOH solution to remove surface impurities, then rinsed with deionized water for 3 times and dried for use. Then, 20 mL of benzophenone ethanol solution was added to 100 mL of acrylic acid aqueous solution, stirred at room temperature, and then the non-woven fabric was added and immersed for 1 h. 2) Take out the non-woven fabric impregnated in step 1) and irradiate the front and back sides with ultraviolet light for 0.5 h; then use anhydrous ethanol for ultrasonic cleaning, and then rinse with deionized water for 3 times and dry for use; 3) 9.9 mg of benzo[1,2-B:3,4-B':5,6-B']terthiophene-2,5,8-trialdehyde and 9.3 mg of an amino compound were placed in a glass tube, a mixture of benzyl alcohol and mesitylene was added, and ultrasonic treatment was performed until the monomers were evenly dispersed. Then, an aqueous solution of acetic acid as a catalyst was added, and ultrasonic treatment was performed for 5 minutes. The dispersion was frozen in a liquid nitrogen bath, and then thawed in a water bath after vacuuming. After repeating the "freeze-vacuum-thaw" process three times, the glass tube was sealed by flame under vacuum, and the sealed glass tube was placed in a 120°C oven for reaction for 3 days; 4) After centrifugation of the solid powder obtained in step 3), the solid powder was extracted with tetrahydrofuran and acetone for 12 h, respectively, and dried in a vacuum oven at 80° C. for 12 h to obtain a COF red powder; 5) placing the obtained COF powder in an EDC ethanol solution, performing ultrasonication at room temperature until the powder is uniformly dispersed, immersing the acrylic acid-modified non-woven fabric obtained in step 2) therein, soaking the solution at room temperature for 24 hours, taking the solution out, washing the solution with anhydrous ethanol for three times, and drying the solution in a vacuum drying oven at 80° C. to obtain the thienyl COF composite fiber; The amino compound in step 3) is one of 2,6-diaminoanthracene, [2,2'-bipyridine]-5,5'-diamine and 2,6-diaminoanthraquinone.

2. The method for preparing a thienyl COF composite fiber according to claim 1, characterized in that: Step 1) The non-woven fabric fiber is made of polypropylene, polyamide, polyacrylonitrile or PET fiber material.

3. The method for preparing a thienyl COF composite fiber according to claim 1, characterized in that: In step 1), the volume percentage concentration of the acrylic acid aqueous solution is 40%, and the concentration of the benzophenone ethanol solution is 15 mg / mL.

4. The method for preparing a thienyl COF composite fiber according to claim 1, characterized in that: In step 2), the wavelength of the UV lamp is 365 nm.

5. The method for preparing a thienyl COF composite fiber according to claim 1, characterized in that: In step 3), the amount of the mixed solution of benzyl alcohol and mesitylene is 1 mL, the volume ratio of benzyl alcohol to mesitylene is 0.9:0.1, the amount of the catalyst acetic acid aqueous solution is 0.1 mL, and the concentration is 6 mol / L.

6. The method for preparing a thienyl COF composite fiber according to claim 1, characterized in that: In step 5), the final concentration of COF powder added was 1 mg / mL, and the concentration of EDC ethanol solution was 2 mg / mL.

7. The thiophene-based COF composite fiber material obtained according to the preparation method according to any one of claims 1 to 6.

8. Use of protective clothing and mask fabrics made from the thienyl COF composite fiber as claimed in claim 7 in photocatalytic antibacterial and degradation of mustard gas simulant.

Citation Information

Patent Citations

  • Two-dimensional covalent organic framework modified flexible fiber fabric and preparation method thereof

    CN110904685A

  • Preparation method of COF graft modified carbon cloth / resin-based friction material

    CN114575158A